Encapsulation of in vitro Plectranthus amboinicus (Lour.) Spreng. shoot apices for propagation and conservation - Arumugam, Greetha; Sinniah, Uma Rani; Swamy, Mallappa Kumara; Lynch, Paul T. (SpringerOpen, 2019)
This investigation demonstrates an efficient method of propagation, short-term conservation, and germplasm exchange for Plectranthus amboinicus (Lour.) Spreng. encapsulated propagules. In vitro-derived shoot apices (shoot tips and nodal segments) which showed 100% survival on MS medium supplemented with 0.4 mg/L 6-benzylaminopurine were selected for encapsulation studies. Shoot apices measuring about 3–5 mm in size showed the ability to break the beads and exhibited 100% survival and regrowth. The combination of 3% (w/v) sodium alginate and 100 mM CaCl2 was found to be ideal for forming uniformally spherical beads, and successive preservation of encapsulated shoot apices into plantlets. The encapsulated shoot tips were relatively more effective than the nodal segments in terms of shoot growth and multiplication. Encapsulated shoot tips retained the ability to regrow (63.3%) for up to 40 days when maintained at 4 °C. Encapsulated shoot tips effectively converted into plantlets on agar medium (78%) and peat moss (58%) under in vitro conditions. Encapsulated shoot tips on agar medium showed a higher shoot regeneration (9.91 ± 0.15 shoots per explant) ability than the peat moss (5.71 ± 0.34 shoots per explant), while the highest rooting (12.16 ± 0.23 roots per explant) was observed on peat moss. Thus, calcium alginate encapsulation holds latent qualities that could be explored to develop a future alternative method of propagation, short-term storage and germplasm distribution for elite genotypes of Plectranthus sp.